Stress Echocardiography for the Diagnosis of Coronary Artery Disease: An Evidence-Based Analysis (Medical Advisory Secretariat, 2010)
In July 2009, the Medical Advisory Secretariat (MAS) began work on Non-Invasive Cardiac Imaging Technologies for the Diagnosis of Coronary Artery Disease (CAD), an evidence-based review of the literature surrounding different cardiac imaging modalities to ensure that appropriate technologies are accessed by patients suspected of having CAD. This project came about when the Health Services Branch at the Ministry of Health and Long-Term Care asked MAS to provide an evidentiary platform on effectiveness and cost-effectiveness of non-invasive cardiac imaging modalities. After an initial review of the strategy and consultation with experts, MAS identified five key non-invasive cardiac imaging technologies for the diagnosis of CAD. Evidence-based analyses have been prepared for each of these five imaging modalities: cardiac magnetic resonance imaging, single photon emission computed tomography, 64-slice computed tomographic angiography, stress echocardiography, and stress echocardiography with contrast. For each technology, an economic analysis was also completed (where appropriate). A summary decision analytic model was then developed to encapsulate the data from each of these reports (available on the OHTAC and MAS website). The Non-Invasive Cardiac Imaging Technologies for the Diagnosis of Coronary Artery Disease series is made up of the following reports, which can be publicly accessed at the MAS website at: www.health.gov.on.ca/mas"> www.health.gov.on.ca/mas or at www.health.gov.on.ca/english/providers/program/mas/mas_about.html: 1. Single Photon Emission Computed Tomography for the Diagnosis of Coronary Artery Disease: An Evidence-Based Analysis. 2. Stress Echocardiography for the Diagnosis of Coronary Artery Disease: An Evidence-Based Analysis. 3. Stress Echocardiography with Contrast for the Diagnosis of Coronary Artery Disease: An Evidence-Based Analysis; 4. 64-Slice Computed Tomographic Angiography for the Diagnosis of Coronary Artery Disease: An Evidence-Based Analysis. 5. Cardiac Magnetic Resonance Imaging for the Diagnosis of Coronary Artery Disease: An Evidence-Based Analysis. Pease note that two related evidence-based analyses of non-invasive cardiac imaging technologies for the assessment of myocardial viability are also available on the MAS website: 1. Positron Emission Tomography for the Assessment of Myocardial Viability: An Evidence-Based Analysis. 2. Magnetic Resonance Imaging for the Assessment of Myocardial Viability: an Evidence-Based Analysis. The Toronto Health Economics and Technology Assessment Collaborative has also produced an associated economic report entitled: The Relative Cost-effectiveness of Five Non-invasive Cardiac Imaging Technologies for Diagnosing Coronary Artery Disease in Ontario [Internet]. Available from: http://theta.utoronto.ca/reports/?id=7 OBJECTIVE: The objective of the analysis is to determine the diagnostic accuracy of stress echocardiography (ECHO) in the diagnosis of patients with suspected coronary artery disease (CAD) compared to coronary angiography (CA). STRESS ECHOCARDIOGRAPHY: Stress ECHO is a non-invasive technology that images the heart using ultrasound. It is one of the most commonly employed imaging techniques for investigating a variety of cardiac abnormalities in both community and hospital settings. A complete ECHO exam includes M-mode, 2-dimensional (2-D) images and Doppler imaging. In order to diagnosis CAD and assess whether myocardial ischemia is present, images obtained at rest are compared to those obtained during or immediately after stress. The most commonly used agents used to induce stress are exercise and pharmacological agents such as dobutamine and dipyridamole. The hallmark of stress-induced myocardial ischemia is worsening of wall motion abnormalities or the development of new wall motion abnormalities. A major challenge for stress ECHO is that the interpretation of wall motion contractility and function is subjective. This leads to inter-observer variability and reduced reproducibility. Further, it is estimated that approximately 30% of patients have sub-optimal stress ECHO exams. To overcome this limitation, contrast agents for LV opacification have been developed. Although stress ECHO is a relatively easy to use technology that poses only a low risk of adverse events compared to other imaging technologies, it may potentially be overused and/or misused in CAD diagnosis. Several recent advances have been made focusing on quantitative methods for assessment, improved image quality and enhanced portability, however, evidence on the effectiveness and clinical utility of these enhancements is limited. EVIDENCE-BASED ANALYSIS: RESEARCH QUESTIONS: 1. What is the diagnostic accuracy of stress ECHO for the diagnosis of patients with suspected CAD compared to the reference standard of CA? 2. What is the clinical utility() of stress ECHO? LITERATURE SEARCH: A literature search was performed on August 28, 2009 using OVID MEDLINE, MEDLINE In-Process and Other Non-Indexed Citations, EMBASE, the Cumulative Index to Nursing & Allied Health Literature (CINAHL), the Cochrane Library, and the International Agency for Health Technology Assessment (INAHTA) for studies published from January 1, 2004 until August 21, 2009. Abstracts were reviewed by a single reviewer and, for those studies meeting the eligibility criteria, full-text articles were obtained. Reference lists were also examined for any relevant studies not identified through the search. INCLUSION CRITERIA: Systematic reviews, meta-analyses, randomized controlled trials, prospective observational studies, retrospective analyses. Minimum sample size of 20 enrolled patients. Comparison to CA (reference standard). Definition of CAD specified as either ≥50%, ≥70% or ≥75% coronary artery stenosis on CA. Reporting accuracy data on individual patients (rather than accuracy data stratified by segments of the heart). English. Human. EXCLUSION CRITERIA: Duplicate studies. Non-systematic reviews, case reports. Grey literature (e.g., conference abstracts). Insufficient data for independent calculation of sensitivity and specificity. Use of ECHO for purposes other than diagnosis of CAD (e.g., arrhythmia, valvular disease, mitral stenosis, pre-operative risk of MI). Transesophageal ECHO since its primary use is for non-CAD indications such as endocarditis, intracardiac thrombi, valvular disorders. Only resting ECHO performed. OUTCOMES OF INTEREST: Accuracy outcomes (sensitivity, specificity, positive predictive value, negative predictive value). Costs. SUMMARY OF FINDINGS: Given the vast amount of published literature on stress ECHO, it was decided to focus on the studies contained in the comprehensive 2007 review by Heijenbrok-Kal et al. (1) as a basis for the MAS evidence-based analysis. In applying our inclusion and exclusion criteria, 105 observational studies containing information on 13,035 patients were included. Six studies examined stress ECHO with adenosine, 26 with dipyridamole and 77 with dobutamine, the latter being the most commonly used pharmacological stress ECHO agent in Ontario. A further 18 studies employed exercise as the stressor.() Based on the available evidence, stress ECHO is a useful imaging modality for the diagnosis of CAD in patients with suspected disease. The overall pooled sensitivity is 0.80 (95% CI: 0.77 – 0.82) and the pooled specificity is 0.84 (95% CI: 0.82 – 0.87) using CA as the reference standard. The AUC derived from the sROC curve is 0.895 and the DOR is 20.64. For pharmacological stress, the pooled sensitivity is 0.79 (95% CI: 0.71 – 0.87) and the pooled specificity is 0.85 (95% CI: 0.83 – 0.88). When exercise is employed as the stress agent, the pooled sensitivity is 0.81 (95% CI: 0.76– 0.86) and the pooled specificity is 0.79 (95% CI: 0.71 – 0.87). Although pharmacological stress and exercise stress would be indicated for different patient populations based on ability to exercise there were no significant differences in sensitivity and specificity. Based on clinical experts, diagnostic accuracy on stress ECHO depends on the patient population, the expertise of the interpreter and the quality of the image.